Spatial analysis of an early middle palaeolithic kill/butchering site: the case of the cuesta de la bajada (Teruel, Spain) - Moclán, Abel (2023)
Kill/butchering sites are some of the most important places for understanding the subsistence strategies of hunter-gatherer groups. However, these sites are not common in the archaeological record, and they have not been sufficiently analysed in order to know all their possible variability for ancient periods of the human evolution. In the present study, we have carried out the spatial analysis of the Early Middle Palaeolithic (MIS 9-8) site of Cuesta de la Bajada site (Teruel, Spain), which has been previously identified as a kill/butchering site through the taphonomic analysis of the faunal remains. Our results show that the spatial properties of the faunal and lithic tools distribution in levels CB2 and CB3 are well-preserved although the site is an open-air location. Both levels show a similar segregated (i.e. regular) spatial point pattern (SPP) which is different from the SPP identified at other sites with similar nature from the ethnographic and the archaeological records. However, although the archaeological materials have a regular distribution pattern, the lithic and faunal remains are positively associated, which is indicating that most parts of both types of materials were accumulated during the same occupation episodes, which were probably sporadic and focused on getting only few animal carcasses at a time.